Dehydrated Human Amniotic Membrane Inhibits Myofibroblast Contraction through the Regulation of the TGFβ‒SMAD Pathway In Vitro - Sarah E. Moreno; Michelle Massee; Thomas J. Koob (Elsevier, 2021)
Excessive fibrosis affects more than 100 million patients yearly, leading to the accumulation of extracellular matrix that compromises tissue architecture and impedes its function. Intrinsic properties of the amniotic membrane have alluded to its potential to inhibit excessive fibrosis; therefore, this study aimed to investigate the effects of dehydrated human amnion/chorion membrane (dHACM) on dermal fibroblasts and their role in fibrotic pathways. Human dermal fibroblasts were stimulated with TGFβ1, triggering myofibroblast-like characteristics in vitro. Subsequent addition of dHACM in the continued presence of TGFβ1 inhibited downstream signaling, leading to a reduction in the expression of known fibrotic and extracellular matrix genes. In addition, dHACM decreased alpha-smooth muscle actin, a stress filament responsible for contractile activity in scarring. The functional outcome of these effects was observed in an ex vivo model for cellular contraction. Hyperactivation of TGFβ signaling increased the contractile capacity of myofibroblasts embedded within a collagen substrate. Simultaneous addition of dHACM treatment prevented the marked contraction, which is likely a direct result of the inhibition of TGFβ signaling mentioned earlier. These observations may support the use of dHACM in the regulation of fibroblast activity as it relates to tissue fibrosis.